Evaluasi Implementasi Program Penguatan Budaya Kerja SMK di Jawa Barat - Nasyaliyah, Laila; Situmorang, Robinson; Nurani, Yuliani (Jurnal Paedagogy, 2023)
This study aims to evaluate the implementation of government assistance programs to strengthen the work culture of vocational schools in West Java in 2020. This research was evaluation research using a goal-oriented evaluation model by Raplh W. Tyler, which used a quantitative approach. Data collection techniques used questionnaires and documentation. Respondents used as data sources were school principals or teachers in charge of the assistance program, with a sample of 10 SMK in West Java. This research data analysis technique used descriptive statistics. The results of the evaluation of this evaluation research were (1) Schools could apply work culture in the learning process and practice according to competency skills and aligned with the needs of the world of work (2) Students gained understanding and ability to apply work culture from the world of work. The conclusion from this research is that the beneficiaries of the assistance program have carried out all the program components properly.